Variação morfológica e assimetria flutuante de abelhas euglossinas (Hymenoptera, Apidae) em diferentes áreas e estações distintas em uma reserva de floresta estacional semidecidual - Silva, Marcela Carlos da (2007)
The survival of organisms in heterogeneous and instable environment requires sometimes physiologic and morphologic adjustment, thus involving complex regulator mechanisms. On the other hand, the organisms themselves also have a kind of ability to resist either genetic disturbs or environmental troubles while in development, producing a phenotype pre determined. The main purpose of this study is to verify whether there have been differences in the size and levels of fluctuating asymmetry (FA) in two species of bees Euglossinae which were collected in two areas with distinct an tropic interferences and in two different seasons of the year in a reserve of Semidecidual Station Forest . The FA is frequently used to stimate stability in the development, besides being a good indicator of environmental impact levels. For each species studies 60 male species were chosen by chance, in whose wings four measurements were done so as to obtain a multi variable indices of size and indices of FA. There were no significant differences in the size of E. nigrita in the different places nor in the different seasons (F=0,568; P=0,454). The results for E. pleosticta indicated significant differences in the size of the bees in the two different seasons (F=20,947; P=0,001), but no differences were observed in the size in relation with the places (F = 0,109; P = 0,743). The male bees of E. pleosticta presented higher indices of size during the hot and wet season. The higher indices of rain and the consequent bigger availability of food during this season could have had an important role over the increase of biomass in E. pleosticta in this period. Regarding the FA, there were no significant differences in the analyzed characters between the places and seasons for both the E. nigrita and E. pleosticta. But for the E. pleosticta there were significant interaction between the season the M3 place. The collected bees in the hot and wet season which were found in the edge of the forest were more asymmetric than the bees collected in the cold and dry season which were found inside the forest. This indicates that the the weather and the a tropic interferences together influence the stability of development of the E. pleosticta. Nevertheless the same does not happen with the E. nigrita, which showed itself more resistant to the environmental interferences in its development program. Thus, its great plastic potential would lessen the stress conditions, allowing the maintenance of its development, as established in great or normal conditions, this way constituting a efficient mechanism of the development stability.